Association between rapid and sustained remission and clinician- and patient-reported outcomes in patients with rheumatoid arthritis: post hoc analysis of data from the SELECT-COMPARE study - Laure Gossec; Jayesh Patel; Aditi Kadakia; Siran Fang; Yi Peng; Sander Strengholt; Peter C. Taylor; Andrew Östör (Arthritis Research & Therapy)
Abstract Background Rapid remission has been shown to be beneficial in patients with early rheumatoid arthritis (RA). This study assessed the association of rapid and sustained remission with long-term clinician- and patient-reported outcomes (CRO/PROs) in patients treated with b/tsDMARDs. Methods This post hoc analysis used pooled data on patients with moderately-to-severely active RA receiving upadacitinib or adalimumab from the SELECT-COMPARE trial (NCT02629159) and its open-label long-term extension (up to 5 years). This study assessed the effect of achieving rapid remission, time to remission, and time in sustained remission on CRO/PROs. Rapid remission was defined as a Disease Activity Score 28 with C-reactive protein (DAS28-CRP) < 2.6 after 12 weeks’ treatment. The outcomes of interest included a variety of PROs, such as pain, fatigue, quality of life, and CROs (28 swollen/tender joint counts). Where available, outcomes were assessed for up to 5 years; mean change in outcomes, as well as adjusted odds ratios (aOR) of achieving minimal clinically important differences (MCIDs) or normative values. Multivariate regression analyses were conducted adjusting for baseline covariates. Results In total, 28% of patients (n/N = 247/865; mean disease duration: 8.2 ± 7.8 years) achieved rapid remission. Rapid remission was associated with significantly greater improvements from baseline in all outcomes at Week 26 and significantly greater odds of achieving MCIDs (aOR range: 2.2–5.6) or normative values (aOR range: 1.6–9.8) in most PROs, including pain, fatigue, and physical functioning, over the variable 5-year follow-up; significantly lower swollen/tender joint counts were also observed. Time to achieve remission was associated with better outcomes: for every month delay in achieving remission, likelihood of achieving MCIDs or normative values decreased, on average, by 13%. Increasing time spent in sustained remission was associated with long-term improvement in CRO/PROs. Conclusions Remission is a key outcome in RA; this study showed that achieving rapid remission, as well as reducing time to achieving remission, was associated with less pain and fatigue, and better physical functioning and quality of life over 5 years. Similarly, increasing time spent in sustained remission correlated with sustained improvement in CRO/PROs. Striving for rapid, sustained remission leads to long-term benefits.